THE EFFECT OF CHEWING GUM ON IMPROVING THE INTESTINE PERISTALTIC AMONG POST CESAREAN SECTIO PATIENTS AT HOSPITAL OF KENDARI CITY - Andi Herman; Budi Santoso; Esty Yunitasari (International Journal of Nursing and Health Services (IJNHS), 2019)
Cesarean section is a surgical intervention that most significantly affects the central nervous system and slows down bowel movements post section Caesarea. Intestinal function in women undergoing section caesarian surgery is essential, starting early. The study aimed at examining the effect of chewing gum on increasing the intestinal peristalsis in post-cesarean section. This study used a quasi-experimental, pre, and post with a control group was applied in this study. Seventy-two samples were recruited using a non-probability sampling such as consecutive sampling. CG was given to the intervention group 3 times, per 3 hours for 5 minutes with a frequency of chewing 30 times. Data analysis was performed and presented in descriptive statistics, and significant findings were computed using the paired t-test. The results showed that the mean Intestine Peristaltic intervention group increases from 11,47+1,647 to 16,61+2,487 after the intervention. Meanwhile, in the control group, the mean Intestine Peristaltic level slightly increases from 11,31+1,470 to 14,22+1,290. The t-test obtained a p-value of 0.000, indicating that there were significant differences in the increase Intestine Peristaltic between the intervention and the control group. Chewing gum can increase intestinal peristalsis in cesarean section patients. Based on the findings, The nurse profession can use chewing gum to become one of the nursing independent interventions because easy. Keywords: cesarean section, peristaltic, chewing gum.